PENERAPAN KEADILAN RESTORATIVE DALAM PENYELESAIAN PERKARA KECELAKAAN LALU LINTAS YANG MENYEBABKAN KORBAN LUKA BERAT DAN MENINGGAL DUNIA (Penelitian di Satlantas Polres Batu Bara) - Ferimon, Ferimon; Mulyadi, Mahmud; Affan, Ibnu (LPPM YPITI, 2021)
Theoretically the existence of restorative justice through mediation of penalties is a new dimension in the Indonesian criminal justice system. However, practically, restorative justice has long been applied in Indonesian society, especially in the scope of customary criminal law. But unfortunately, the settlement of traffic accident cases that have caused serious injuries and death through mediation by the law has not yet been integrated in criminal law. The problems in this study are, how do the legal arrangements and the application of restorative justice as well as the obstacles to the implementation of restorative justice in the settlement of traffic accident cases that cause serious injuries and deaths at the Police Traffic Police Traffic Unit?This type of research is empirical juridical research, while the nature of the study is descriptive analysis. Based on the results of the study, The legal basis for implementing restorative justice in the settlement of traffic accident cases refers to the discretionary authority of the police regulated in Article 18 of the Police Law and Circular Letter of the National Police Chief Number 8 of 2018 regarding the Application of Restorative Justice Justice in the Settlement of Criminal Cases. The implementation of restorative justice in the settlement of cases of traffic accidents that cause serious injuries and deaths at the Traffic Police Traffic Unit of the Coal Police Station has gone according to community expectations. In the case of a traffic accident that results in fatalities, restorative justice cannot be carried out. Barriers to the implementation of restorative justice in the settlement of traffic accident cases that cause serious injuries and deaths at the Traffic Unit of the Coal of Polres are influenced by two factors, namely the legal substance that has not been supported and the legal culture of the community which tends to have a paradigm of material values ​​in determining the size of justice.